101 Role of cardiac autonomic function in pathophysiology of permanent AF. (4th June 2021) - Khan, Ahsan; Junejo, Rehan; Thomas, Neil; Fisher, James; Lip, G.
Abstract : Introduction: Atrial fibrillation (AF) is the commonest abnormal heart rhythm with significant related morbidity and mortality. There is increasing evidence that abnormalities of the cardiac autonomic nervous system (ANS) are involved in the pathogenesis of AF. Exploring the ANS is possible through heart rate variability (HRV) evaluation. We aimed to investigate whether HRV is more abnormal in patients with permanent AF compared to paroxysmal AF. Methods: In a cross-sectional comparison, we studied two patient groups: permanent AF (n = 30) and paroxysmal AF (n = 31). Time-domain, frequency-domain and non-linear measures of HRV were determined using eMotion Faros ECG sensor. Participant's breathing was controlled with a metronome. Data was analysed using SPSS software. Results: Time-domain and non-linear indices of HRV were significant higher in permanent AF group compared to paroxysmal AF ( table 1 ). Permanent AF was the only independent predictor of HRV on multivariable analysis in this cohort of patients (p=0.006). Conclusions: HRV indices were significantly higher in permanent AF compared to paroxysmal AF which may suggest pronounced cardiac autonomic influence in the pathophysiology of permanent AF. Conflict of Interest: None